Transformations in slavery a history of slavery in Africa - Lovejoy, Paul E. (African studies series, 2012)
"This history of African slavery from the fifteenth to the early twentieth centuries examines how indigenous African slavery developed within an international context. The new edition revises statistical material and incorporates recent research"--